Ketersediaan beras menuju kemandiriaan pangan: pendekatan sistem dinamik - Risna Rahmatul Wajdah (Analisis Kebijakan Pertanian, 2024)
The demand for rice in Indonesia continues to escalate, while its availability is confronted by various challenges. Production, productivity, and the area of rice fields have been on a decline, concurrently with a growing population. This research aimed to develop and analyze the availability of rice and formulate policy recommendations for achieving food (rice) resiliency. This research method used a dynamic systems approach assisted by the Powersim 10 and Vensim PLE analysis tools. Model validation was carried out for the 2018-2022 period. The model was simulated until 2045. The simulation result shows that at the basic condition model, in 2045, rice supply based on domestic production will be in deficit. Therefore, it is recommended that the government, takes steps to balance rice production and demand by increasing rice production substantially through the construction of rice fields outside Java, effectively enforcing regulations regarding land conversion, providing intensive agricultural extension for farmers to support a sustainable rice farming system, and maintaining stability in paddy and rice prices. Additionally, on the demand side, efforts can be made by carrying out socialization and promotion of consumption diversification based on local food sources to farmers and food industry entrepreneurs.
Keywords: dynamic sytems; availability of rice; food resiliency; management strategy; kemandirian pangan; ketersediaan beras; sistem dinamik; strategi manajemen